PEMANFAATAN TUMBUHAN SEBAGAI OBAT TRADISIONAL OLEH MASYARAKAT SUKU MAYBRAT DI KAMPUNG RENIS DISTRIK MARE KABUPATEN SORONG SELATAN - Frengki L.K. Hara; Jan H. Nunaki; M.J. Sadsoeitoeboen (FMIPA Universitas Papua, 2009)
The aims of the research were to identify the main plant species which are used as Traditional medicines by Maybrat tribe in Sorong, to describe the method of preparation and uses of some of the medicinal plants, and to study methods for passing the knowledge of traditional medicines amongst the tribe. The tribe has used 47 species of medicines plants from 30 families. Part of medicines plant used by leaf 28 plant species, braise is the way of a lot of gathering medicines 10 species, without gathered by as much 11 species and way of medication of a lot of drinkedly 19 species. From 47 species of medicines plant exploited by tribe Maybrat in the reality its 1 species own the economic value that is Afa ati (Laportea indica).